Perancangan User Experience Aplikasi Bus Antar Kota Menggunakan Metode Design Thinking - Muhammad Reza; Donaya Pasha; Qadhli Jafar Adrian (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
PO Puspa Jaya has not made maximum use of internet technology as a means of developing services to passengers, almost all activities in the process of inter-city bus activities are carried out manually, this has resulted in a lack of services provided to customers so that it can reduce the number of customers and ultimately lose out in competition with other companies. The purpose of this research is to design a User Experience for intercity bus applications at PO Puspa Jaya using the Design Thinking method which includes low to high-fidelity prototypes. The results of the application so that it provides convenience and increases satisfaction in inter-city bus services provided by PO Puspa Jaya. The results of measuring the efficiency of the average completion rate are 97.22 percent. Measurement of satisfaction, measured at the level of user satisfaction when interacting or human interaction with applications using the System Usability Scale (SUS) obtained a score of 80.625 points where the score has reached the standard value of the Experience Questionnaire (UEQ), measured at the level of user satisfaction when interacting or human interaction with the application obtained a score of 74.81 where the score has achieved a good grade standard.